Penggunaan Komunikasi Nonverbal pada Penyandang Tunawicara dalam Film Return of the Cuckoo - Wulandari, Ratna Dewi Eka; Fatimah, Diva Nur; Mintowati, Maria (LPPM STKIP PGRI Bandar Lampung, 2024)
The film Return of the Cuckoo (2016) highlights the experiences of individuals with speech impairments in communicating. This study discusses how speech-impaired characters in the film use nonverbal communication to express emotions and build relationships with other characters. The focus of this study is the interaction of characters who use sign language to convey emotions. Through a qualitative approach with a descriptive method to explore the phenomenon of the use of sign language. In the film scene, it was found that sign language, body gestures and facial expressions were the main tools for speech-impaired characters in conveying various emotions, ranging from happiness, anxiety, sadness, to gratitude. The use of nonverbal communication not only enriches the characterization of the character, but also provides insight into how individuals with verbal limitations can communicate effectively. The results of the study show that nonverbal language such as gestures, hand movements, facial expressions, play an important role in conveying emotions. The use of nonverbal communication not only functions as a means of conveying messages, but also builds deep emotional relationships between characters. This study is expected to contribute to the study of nonverbal communication in the world of film or cinema and can enrich understanding of the importance of nonverbal communication in supporting social relationships.